Propensity score-matched comparison of robotic- and video-assisted thoracoscopic surgery, and open lobectomy for non-small cell lung cancer patients aged 75 years or older - Pan, Hanbo; Gu, Zenan; Tian, Yu; Jiang, Long; Zhu, Hongda; Ning, Junwei; Huang, Jia; Luo, Qingquan (Frontiers in Oncology, 2022)
Introduction: Although robot-assisted thoracoscopic surgery (RATS) has been widely applied in treating non-small cell lung cancer (NSCLC), its advantages remain unclear for very old patients. The present study aims to access the feasibility and oncological efficacy of RATS for NSCLC patients aged ≥75 years. Methods: Pathological IA-IIIB NSCLC patients aged ≥75 years who underwent RATS, video-assisted thoracoscopic surgery (VATS), or open lobectomy (OL) between June 2015 and June 2021 in Shanghai Chest Hospital were included. Propensity score matching (PSM, 1:1:1 RATS versus VATS versus OL) was based on 10 key prognostic factors. Perioperative outcomes and long-term survival were evaluated. Results: A total of 504 cases (126 RATS, 200 VATS, and 178 OL) were enrolled, and PSM led to 97 cases in each group. The results showed that RATS led to: 1) the shortest operation duration (p <0.001) and the least blood loss (p <0.001); 2) the shortest ICU stay (p = 0.004), chest tube drainage duration (p <0.001), and postoperative stay (p <0.001), and the most overall costs (p <0.001); 3) the lowest incidence of postoperative complications (p = 0.002) and pneumonia (p <0.001). There was no difference in resection margins, reoperation rates, intraoperative blood transfusion, and volume of chest tube drainage among the three groups. Moreover, OL dissected the most N1 (p <0.001), N2 (p <0.001), and total (p <0.001) lymph nodes (LNs), while RATS assessed more N1 (p = 0.009) and total (p = 0.007) LNs than VATS. The three surgical approaches dissected a similar number of N1, N2, and total LN stations, and led to a comparable incidence of postoperative nodal upstaging. Finally, the three groups possessed comparable 5-year disease-free (DFS) and overall survival (OS). Further subgroup analysis found no difference in DFS and OS among the RATS, VAST, and OL groups, and multivariable analysis also showed that the surgical approach was not independently correlated with DFS or OS. Conclusion: RATS led to favorable perioperative outcomes and achieved similar 5-year outcomes compared with VATS and OL, therefore was a feasible and oncological effective surgical approach for NSCLC patients aged ≥75 years.